Strategi Promosi Dalam Mempertahankan Penjualan Nasi Soto Tangkar Mang Endi - Nazwa Nur Fadhila; Nuri Salamah; Dwi Epty Hidayaty; Santi Pertiwi Hari Sandi (Madani: Jurnal Ilmiah Multidisiplin, 2023)
This observation aims to explain the strategy and steps to optimize the customer experience in marketing Nasi Soto Tangkar, with a focus on the Promotional Strategy used because the Internet has been used by various groups of people including MSME entrepreneurs in the regions. However, the lack of insight and education for MSME entrepreneurs causes the use of the internet to be not optimal in supporting business processes in order to increase the profits achieved by MSME actors. In this article, the author discusses the Importance of Marketing in SMEs Nasi soto tangkar mang endi and the importance of quality food, good customer service, pleasant dining experiences, effective advertising and communication, and the importance of regular feedback and reviews. Implementing these steps, companies in the nasi soto tangkar industry can improve their marketing as well as customer satisfaction and build strong brand loyalty. This article provides practical guidance to business owners to improve customer experience, which in turn will increase business success and growth in the Nasi Soto Tangkar business as well as in facing competitors in the market, especially culinary.